University students' perception of animal welfare and opinions on consumption of milk and dairy products - Şeker, Pınar; Güler, Hakan; Köseman, Abdurrahman; Şeker, İbrahim (İstanbul Veteriner Hekimler Odası, 2021)
The aim of this study is to determine the opinions of university students on the consumption of milk and dairy products within the scope of animal welfare. The research was carried out with 361 randomly selected students from Samsun Ondokuz Mayıs University, Turkey, using a face-to-face questionnaire. In the study, the rate of students who think that, they do not have information about the presence and amount of cholesterol in milk and dairy products was 77.35%, milk and dairy products contain all the nutritional elements was 35.62%, UHT milk is not spoiled for a long time due to heat treatment was 28.90%, milk, cheese, yoghurt prices are normal were 63.34%, 40.41%, 68.31%, respectively, there was a welfare problem in farm animals was 56.00%. Also, the rate of students who want label information about milk and dairy products produced from animals raised under welfare conditions was 75.43%. The rates of students who can pay up to 10%, 11-25%, and more than 25% for milk and dairy products because they are suitable for animal welfare were determined as 64.74%, 26.14% and 9.12%, respectively. As a result, it was determined that university students' perceptions of animal welfare and their views on milk and dairy products consumption were generally at an acceptable level. However, more information and necessary training support should be provided to bring them to the desired level.
Keywords: Veterinary Surgery; Veteriner Cerrahi